The peptide binding site of the substance P (NK-1) receptor localized by a photoreactive analogue of substance P: presence of a disulfide bond. - Boyd, N D (1996)
Substance P (SP) is a neuropeptide that mediates multiple physiological responses including transmission of painful stimuli and inflammation via an interaction with a receptor of known primary sequence. To identify the regions of the SP receptor, also termed the NK-1 receptor, involved in peptide recognition, we are using analogues of SP containing the photoreactive amino acid p-benzoyl-L-phenylalanine (Bpa). In the present study, we used radioiodinated Bpa8-SP to covalently label with high efficiency the rat SP receptor expressed in a transfected mammalian cell line. To identify the amino acid residue that serves as the site of covalent attachment, a membrane preparation of labeled receptor was subjected to partial enzymatic cleavage by trypsin. A major digestion product of 22 kDa was identified. Upon reduction with 2-mercaptoethanol the mass of this product decreased to 14 kDa. The 22-kDa tryptic fragment was purified in excellent yield by preparative SDS/PAGE under nonreducing conditions. Subcleavage with Staphylococcus aureus V8 protease and endoproteinase ArgC yielded fragments of 8.2 and 9.0 kDa, respectively. Upon reductive cleavage, the V8 protease fragment decreased to 3.0 kDa while the endoproteinase ArgC fragment decreased to 3.2 kDa. Taking into consideration enzyme specificity, molecular size, determination of the presence or absence of N-glycosylation sites, and recognition by antibodies to specific sequences of the SP receptor, the V8 protease fragment is Thr-173 to Glu-183, while the endoproteinase ArgC fragment is Val-178 to Arg-190. These two fragments share the common sequence Val-Val-Cys-Met-Ile-Glu (residues 178-183). The site of covalent attachment of radioiodinated Bpa8-SP is thus restricted to a residue within this overlap sequence. The data presented here also establish that the cysteine residue in this sequence Cys-180, which is positioned in the middle of the second extracellular loop, participates in a disulfide bond that links the first and second extracellular loops of the receptor.